Ответ:
x₂ = 2
p = 7
Объяснение:
х² + px - 18 = 0
x₁ = -9
(-9)² - 9p - 18 = 0
81 - 9p - 18 = 0
-9p + 63 = 0
-9p = -63
Решим уравнение.
x² + 7x - 18 = 0
D = 7² - 4 * 1 * (-18) = 49 + 72 = 121 = 11²
x₁ = (-7 - 11) / 2 = -18 / 2 = -9
x₂ = (-7 + 11) / 2 = 4 / 2 = 2
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
x₂ = 2
p = 7
Объяснение:
х² + px - 18 = 0
x₁ = -9
(-9)² - 9p - 18 = 0
81 - 9p - 18 = 0
-9p + 63 = 0
-9p = -63
p = 7
Решим уравнение.
x² + 7x - 18 = 0
D = 7² - 4 * 1 * (-18) = 49 + 72 = 121 = 11²
x₁ = (-7 - 11) / 2 = -18 / 2 = -9
x₂ = (-7 + 11) / 2 = 4 / 2 = 2